Incidence, risk factors, management and outcomes of amniotic‐fluid embolism: a population‐based cohort and nested case–control study. (12th February 2015) - Fitzpatrick, KE; Tuffnell, D; Kurinczuk, JJ; Knight, M
Abstract : Objective: To describe the incidence, risk factors, management and outcomes of amniotic‐fluid embolism (AFE) over time. Design: A population‐based cohort and nested case–control study using the UK Obstetric Surveillance System (UKOSS). Setting: All UK hospitals with obstetrician‐led maternity units. Population: All women diagnosed with AFE in the UK between February 2005 and January 2014 ( n  = 120) and 3839 control women. Methods: Prospective case and control identification through UKOSS monthly mailing. Main outcome measures: Amniotic‐fluid embolism, maternal death or permanent neurological injury. Results: The total and fatal incidence of AFE, estimated as 1.7 and 0.3 per 100 000, respectively, showed no significant temporal trend over the study period and there was no notable temporal change in risk factors for AFE. Twenty‐three women died (case fatality 19%) and seven (7%) of the surviving women had permanent neurological injury. Women who died or had permanent neurological injury were more likely to present with cardiac arrest (83% versus 33%, P  < 0.001), be from ethnic‐minority groups (adjusted odds ratio [OR] 2.85, 95% confidence interval [95% CI] 1.02–8.00), have had a hysterectomy (unadjusted OR 2.49, 95% CI 1.02–6.06), had a shorter time interval between the AFE event and when the hysterectomy was performed (median interval 77 minutes versus 248 minutes, P  = 0.0315), and were less likely to receive cryoprecipitate (unadjusted OR 0.30, 95% CI 0.11–0.80). Conclusion: There is no evidence of a temporal change in the incidence of or risk factors for AFE. Further investigation is needed to establish whether earlier treatments can reverse the cascade of deterioration leading to severe outcomes.